2018
DOI: 10.3390/su10124552
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effects of the Built Environment on PM2.5 and PM10: A Case Study of Seoul Metropolitan City, South Korea

Abstract: Air pollution has a major impact on human health and quality of life; therefore, its determinants should be studied to promote effective management and reduction. Here, we examined the influence of the built environment on air pollution by analyzing the relationship between the built environment and particulate matter (i.e., PM2.5 and PM10). Air pollution data collected in Seoul in 2014 were spatially mapped using geographic information system tools, and PM2.5 and PM10 concentrations were determined in individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…The level of air pollution in Seoul has been increasing, as mentioned above, and the air pollution caused by the PM fraction has been increasing significantly. The average PM levels in Seoul have increased significantly over the years, and reached more than three times (32 µm/m 3 ) the WHO standard of 10 µm/m 3 for the annual mean both in 2017 and 2018 [38].…”
Section: Social Benefits Of Fine Particulate Matter (Pm) Mitigationmentioning
confidence: 99%
“…The level of air pollution in Seoul has been increasing, as mentioned above, and the air pollution caused by the PM fraction has been increasing significantly. The average PM levels in Seoul have increased significantly over the years, and reached more than three times (32 µm/m 3 ) the WHO standard of 10 µm/m 3 for the annual mean both in 2017 and 2018 [38].…”
Section: Social Benefits Of Fine Particulate Matter (Pm) Mitigationmentioning
confidence: 99%
“…However, according to the land use data, residential areas showed a significant positive correlation with PM 2.5 concentration in DKI Jakarta. Studies of PM, the correlation have demonstrated high correlation between PM 2.5 level and residential areas, especially in high-density residential areas [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the rapid economic development based on industry and urbanization, serious particle pollution has occurred, especially in metropolitan areas such as Beijing, and has attracted increasing attention from the public, government, and scientific institutions worldwide. The pollution problem is not conducive to the construction of an eco-friendly society and the development of sustainability [1]. The atmospheric particles (particulate matter, PM) have posed a threat to climate change and human health [2][3][4], especially PM 10 and PM 2.5 , which are defined as the particles with aerodynamic diameters of less than 10 µm (PM 10 ) and 2.5 µm (PM 2.5 ), respectively [5].…”
Section: Introductionmentioning
confidence: 99%